Perspectives From COPD Subjects on Portable Long-Term Oxygen Therapy Devices - AlMutairi, Hejab J; Mussa, Constance C; Lambert, Clement Tm; Vines, David L; Strickland, Shawna L (Respiratory care, 2018)
Oxygen therapy for patients with COPD and severe hypoxemia requires the use of oxygen delivery devices that allow mobility as needed. However, the characteristics of some devices may limit the freedom of individuals to be as physically active as they desire. Limited mobility may negatively affect the perceived quality of life of individuals with COPD. The aim of this study was to understand perceived limitations that patients with COPD experience in using long-term oxygen therapy (LTOT) devices. We performed a qualitative analysis of 311 responses to an open-ended question from a previously deployed electronic survey designed to investigate how LTOT devices affect oxygen-dependent patients with COPD. Our thematic analysis was facilitated by NVivo, a qualitative data analysis software package. This involved identifying patterns and themes within the robust, text-rich data from the open-ended survey question regarding the survey subjects' experiences with their LTOT devices. Cluster analysis was also performed to highlight relationships between various concepts. Themes generated revealed that subjects experienced decreased mobility, which resulted in feelings of decreased autonomy and isolation. We also found that subjects perceived a decrease in quality of life due to their described experience of portable oxygen cylinders being heavy and cumbersome. Subjects described feelings of fear and anxiety due to insufficient support for breathing provided by pulse-dose portable oxygen concentrators, as well as portable oxygen cylinders that run out before they are able to complete errands and other activities of daily living. Some subjects also reported that they willingly pay for liquid oxygen systems out-of-pocket because of the mobility it affords, which in their perception improves their quality of life. Oxygen-dependent individuals with COPD may be at risk of adverse outcomes associated with decreased mobility encouraged by unsatisfactory physical and technical characteristics of portable oxygen cylinders and concentrators.